Theremin in the Press: Instrument remediation and code-instrument transduction. - Oliver La Rosa, Jaime E. (Organised Sound, 2018)
This article shows how the theremin as a new musical medium enacted a double logic throughout its century-old techno-cultural life. On the one hand, in an attempt to be a 'better' instrument, the theremin imitated or remediated traditional musical instruments and in this way affirmed the musical values these instruments materialised; simultaneously, by being a new and different medium, with unprecedented flexibility for designing sound and human–machine interaction, it eroded and challenged these same values and gradually enacted change. On the other hand, the theremin inadvertently inaugurated a practice of musical instrument circulation using electronics schematics that allowed for the instrument's reproduction, starting with the publication of schematics and tutorials in amateur electronics magazines and which can be seen as a predecessor to today's circulation of open source code. This circulation practice, which I call instrument-code transduction, emerged from and was amplified by the fame the theremin obtained using its touchless interface to imitate or remediate traditional musical instruments, and in turn, this circulation practice has kept the instrument alive throughout the decades. Thus remediation and code-instrument transduction are not just mutually dependent, but are in fact, two interdependent processes of the same media phenomenon. Drawing from early reactions to the theremin documented in the press, from new media theory, and from publications in amateur electronics, this article attempts to use episodes from the history of the theremin to understand the early and profound changes that electric technologies brought to the concept of musical instruments at large.